Commissioning experience of the X-ray volume imaging system of an image-guided radiotherapy capable linear accelerator. Issue 1 (13th March 2021) - Raina, Payal; Sahoo, Susanta Kumar
Abstract: Aim: An image-guided radiotherapy capable linear accelerator was installed at our hospital which is equipped with an X-ray volumetric imaging (XVI) system. The aim of this study was to describe the results of acceptance tests which were carried out on the XVI facility to verify the manufacturer's specification. Materials and methods: The commissioning test had six elements: system safety, geometric accuracy, image quality, registration and correction accuracy, X-ray tube and generator performance, and quality assurance (QA) procedures. Results: We had satisfactory results for all the tests. The system passed the safety testes, and the agreement of isocentres was found to be within the tolerance limit. Imaging quality was acceptable. Registration and correction accuracy was tasted with indigenously developed phantom and positioned accurately at isocentre. X-ray tube and generator test results showed that the tube was performing properly. Findings: The described tests represent that the performance of the system is maintained at acceptable levels.